2015
DOI: 10.1111/imj.12791
|View full text |Cite
|
Sign up to set email alerts
|

Removal of body surface area normalisation improves raw‐measured glomerular filtration rate estimation by the Chronic Kidney Disease Epidemiology Collaboration equation and drug dosing in the obese

Abstract: The CKD-EPI without normalisation (CKD-EPI_noBSA) equation was superior to the CKD-EPI equation in estimating raw-measured Tc-DTPA GFR (mL/min).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…However, de‐indexation is crucial because the performance of the CKD‐EPI equation (in ml min –1 1.73 m –2 ) compared with the non‐indexed mGFR equations (ml min –1 ) is significantly worse, and underestimates the mGFR more (data not shown). The same results have been demonstrated in a recent study by Chew‐Harris et al . In this study, only 78 obese patients were included but the authors showed that the CKD‐EPI without normalization (in ml min −1 ) was superior to the CKD‐EPI equation indexed (in ml min −1 1.73 m –2 ) in estimating the absolute clearance of 99 mTc‐DTPA (in ml min −1 ).…”
Section: Discussionsupporting
confidence: 84%
“…However, de‐indexation is crucial because the performance of the CKD‐EPI equation (in ml min –1 1.73 m –2 ) compared with the non‐indexed mGFR equations (ml min –1 ) is significantly worse, and underestimates the mGFR more (data not shown). The same results have been demonstrated in a recent study by Chew‐Harris et al . In this study, only 78 obese patients were included but the authors showed that the CKD‐EPI without normalization (in ml min −1 ) was superior to the CKD‐EPI equation indexed (in ml min −1 1.73 m –2 ) in estimating the absolute clearance of 99 mTc‐DTPA (in ml min −1 ).…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with the previous literature, which demonstrated that the CKD‐EPI equation non‐normalized to the BSA correlated more closely with the Cockcroft‐Gault equation than did other formulae . Similarly, in another study, the non‐normalized CKD‐EPI equation (mL/min) was found superior to the normalized CKD‐EPI equation in estimating GFR (mL/min per 1.73 m 2 ) for drug dosing . Using the GFR (mL/min) as the reference for dosing, the CKD‐EPI with the removal of BSA normalization (mL/min) was associated with greater dosing concordance of carboplatin .…”
Section: Discussionmentioning
confidence: 90%
“…35 Similarly, in another study, the non-normalized CKD-EPI equation (mL/ min) was found superior to the normalized CKD-EPI equation in estimating GFR (mL/min per 1.73 m 2 ) for drug dosing. 36 Using the GFR (mL/min) as the reference for dosing, the CKD-EPI with the removal of BSA normalization (mL/min) was associated with greater dosing concordance of carboplatin. 36 The non-normalized CKD-EPI (mL/min) provided results, which were less biassed and comparable at predicting GFR (mL/min) at higher levels of GFR and body mass index.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Renal function was assessed using serum creatinine and estimated glomerular filtration rate by the CKD‐EPI formula (Levey et al ., ). Additionally, the CKD‐EPI without adjustment for body surface area (BSA) was calculated, as it improves accuracy of eGFR in obese subjects (Chew‐Harris et al ., ). As there was no association of the aforementioned baseline renal function parameters with baseline CAF (Figure S1), all participants were included in the analytic sample.…”
Section: Methodsmentioning
confidence: 97%